2015
DOI: 10.14411/fp.2015.002
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterisation of Cryptosporidium (Apicomplexa) in children and cattle in Romania

Abstract: To investigate the transmission of species of Cryptosporidium Tyzzer, 1907 in Timis County, Romania, 48 isolates of Cryptosporidium coccidia from 11 children, 29 calves and eight pigs were characterised by molecular analysis of two loci (SSU rRNA and 60-kDa glycoprotein gene). Overall, 22 isolates were amplified and sequence analyses revealed that all isolates were Cryptosporidium parvum Tyzzer, 1912. Two subtype families were identified, IIa and IId. Subtype IIdA22G1 (n = 4) was the single C. parvum subtype f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
16
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 27 publications
4
16
0
1
Order By: Relevance
“…Molecular characterisation of five isolates indicated the presence of species C. parvum (n = 3) and C. ubiquitum (n = 2) [88]. Vieira et al has also reported the presence of the C. parvum subtype IIdA22G1 in faecal samples of four children under 12 years of age from Timiş County in this area of Romania [89]. …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Molecular characterisation of five isolates indicated the presence of species C. parvum (n = 3) and C. ubiquitum (n = 2) [88]. Vieira et al has also reported the presence of the C. parvum subtype IIdA22G1 in faecal samples of four children under 12 years of age from Timiş County in this area of Romania [89]. …”
Section: Resultsmentioning
confidence: 99%
“…Research focusing on livestock is limited and mostly involves the western [89,92-94], central and north-western [95] regions of the country. The methods applied included non-molecular (conventional acid-fast staining and classical microscopic examination, copro-antigen detection immunoassays) and molecular tools (PCR-restriction fragment length polymorphism (RFLP), DNA sequencing).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Among them, calves in most industrialised countries are commonly infected with IIa subtypes, especially subtype IIaA15G2R1 (Xiao, 2010). In addition, IId subtypes have been identified in dairy calves in some countries such as Sweden, Turkey, Romania and Egypt (Bjorkman et al, 2015;Vieira et al, 2015;Ibrahim et al, 2016;Taylan-Ozkan et al, 2016). In contrast, pre-weaned dairy calves in China are commonly infected with C. bovis, and when they are infected with C. parvum, almost exclusively with IId subtypes, especially IIdA15G1 and IIdA19G1 In 2016, a diarrhea outbreak was identified in neonatal dairy calves on a large dairy farm in Jiangsu Province, China.…”
Section: Introductionmentioning
confidence: 99%
“…Inwazje C. parvum u pozostałych gatunków zwierząt gospodarskich i towarzyszących Wprowadzenie metod molekularnych do diagnostyki parazytologicznej pozwoliło na identyfikację C. parvum również u innych gatunków zwierząt niż przeżuwacze. Zarażenia C. parvum w stadach trzody chlewnej są na ogół rzadkie (70,87,107,115), z ekstensywnością inwazji na poziomie stada nie przekraczającą 1,4% (111). Poza Europą wynosi ona od 5,4% (Stany Zjednoczone) do 33,2% w Japonii (5, 40).…”
Section: Ryc 1 Mapa Polski Przedstawiająca Poszczególne Regiony Kraunclassified